Dramaturgy of Cirebon Teenage Consumer Behavior in Building Self-Image on Instagram - Wahyuningtyas, Novi Kusuma; Ifrohh, Iif Al; Salsabilla, Ghina; Nurfalah, Farida; Hermawan, Abdul Jalil (International Journal of Social Service and Research, 2024)
Instagram is just one of several social media programmes made possible by the latest developments in digital technology. Instagram is more than just a virtual communication tool, but helps teenagers also build their self-image through its many functions. This study aims to uncover how Cirebon teenagers' self-image building works on Instagram, as well as their purchasing habits. The research methodology, particularly the qualitative approach. Results were obtained from an extensive literature review, in-depth interviews, and participant observation. Erving Goffman's dramaturgical perspective was used to examine the data obtained. Teenagers in Cirebon use Instagram as a dramaturgical tool to shape their self-image, according to the research conclusion. Their front stage consistently displays positive aspects and the best material, helping them cultivate a positive self-image and get positive reactions from fans. In addition, Instagram users' real lives are very different from their Instagram appearances, and often users do not want other users to know the ins and outs of their personal lives, including the steps used to create their Instagram appearances.